Sincretismo religioso brasileiro: um estudo através das veredas de Grande Sertão - Carvalho, Juliana Barros Prata (2007)
This work is an attempt to understand Brazilian religious syncretism via Grande Sertão: Veredas . Therefore the essay tries to establish a metaphoric parallel between syncretic and religious plurality contained in João Guimarães Rosa s only romance and Brazilian religious syncretism. This essay is focused on the area of Science of Religion but because it uses a romance - which belongs to the field of literature - as a tool it dialogs with that field of study. The bridge between fiction and reality is established as a live link in constant transformation. Both the characters of the book and the Brazilian people are treated here as beings in a process of discovery of their human identity, as a work-in-progress, under the light of the work of Darcy Ribeiro, Gilberto Freyre and other theorists. A fundamental part of such discovery is the way through which individuals try to relate to objects which are thought to have religious transcendence. Such process will be an object of work with emphasis on syncretism. The concepts of racially-mixed ancestry and religion will also be explored. The conclusions reached in this work rather than absolute and conclusive answers to the questions proposed are long, open paths to be covered. The investigation about religious syncretism using Grande Sertão: Veredas as a tool is only possible via metaphor. Additionally the viability of this essay depends on the assumption that the Brazilian population is necessarily mestizo